(Invited) Directly Silicon Nitride Waveguide Coupled Ge Photodiode for Non-SOI PIC and Epic Platforms. (8th September 2020) - Lischke, Stefan; Knoll, Dieter; Mai, Christian; Voigt, Karsten; Hesse, Anne; Georgieva, Galina; Peczek, Anna; Zimmermann, Lars
Abstract : A Ge photodiode, directly coupled to a silicon nitride waveguide, showing more than 67 GHz bandwidth is demonstrated. This paves the way for utterly new SiN waveguide platform based applications. By light feeding through SiN waveguides, the new photodiode can also be a key enabler for a bulk-Si based, monolithically integrated electronic-photonic integrated circuit platform. We show that the new devices, fabricated on bulk-Si, provide the same bandwidths as Si waveguide coupled SOI based reference Ge photodiodes. However, their O-band responsivity is 0.3 A/W, which is about three times lower compared to the SOI wave-guide coupled devices. We attribute this effect mainly to substrate leakage, being confirmed by simulations. We demonstrate that bulk-Si based diodes can be fabricated with high yield and low metrics tolerances.